Effect of Sn Addition on Phase Transformation Behavior of Equiatomic Ni-Ti Shape Memory Alloy - Ali Abadi aljubouri; safa hasan mohammed; mudhafar ali mohammed (مجلة بغداد للعلوم)
Sn effect on the phase transformation behavior, microstructure, and micro hardness of equiatomic Ni-Ti shape memory alloy was studied. NiTi and NiTiSn alloys were produced using vacuum induction melting process with alloys composition (50% at. Ni, 50% at.Ti) and (Ni 48% at., Ti 50% at., Sn 2% at.). The characteristics of both alloys were investigated by utilizing Differential Scanning Calorimetry, X- ray Diffraction Analysis, Scanning Electron Microscope, optical microscope and vicker's micro hardness test. The results showed that adding Sn element leads to decrease the phase transformation temperatures evidently. Both alloy samples contain NiTi matrix phase and Ti2Ni secondary phase, but the Ti2Ni phase content decreases with Sn addition and this is one of the reasons that leads to decrease the micro hardness of alloy with adding Sn element in a noticeable manner. The micro hardness decreases from 238.74 for NiTi equiatomic alloy to 202 for NiTiSn alloy after heat treatment.